ICT-alan rakennemuutos: Mihin ex-nokialaiset päätyivät? - Jyrki Ali-Yrkkö; Natalia Kuosmanen; Mika Pajarinen (The Research Institute of the Finnish Economy (ETLA), 2021)
– This study examines the employment status of workers who left Nokia during the period 2009-2014. The results reveal that the workers were quite successful in finding employment. According to the latest available data, more than three-quarters of these individuals found a new job, while the share of unemployed was 9.6 percent. The remaining share of ex-employees retired or started to study. Workers with higher education and workers who had held senior officer positions at Nokia were more successful in finding a new job than others. New jobs were often found in the service sector. Some regional differences existed in the employment of the former Nokia employees: finding employment was more successful in North Ostrobothnia, Uusimaa and Central Finland than in Southwest Finland.
Keywords: J01; J21; J23; J64; L16; 330; ICT; Structural change; Nokia; Employment; Employee; Personnel; Find employment